Estimating the total cost of imaging services of a hospital using the time-driven activity-based costing method (TDABC) in 2018 - Sanaz Zargar balaye jame; Nader Markazi moghaddam; Hesam SHarifnia; Mehrdad KHoshian (Tehran University of Medical Sciences, 2023)
Background and Purpose: Medical imaging is one of the most expensive sections of a hospital due to the use of superior technology, specialized personnel, and adherence to special protective regulations, all of which have a direct impact on the diagnosis and treatment of diseases. Time-driven activity-based costing (TDABC) provides an overview of hospital activities, enabling the identification and management of costs and resources with greater accuracy and ease. The purpose of this study is to examine the total costs of services and the unused capacity of resources to provide financial management solutions for hospital administrators. Materials and Methods: This descriptive and retrospective study was conducted on the statistics and accounting data of a general hospital in Tehran in 2018. The study falls under the category of applied research due to the potential use of the results in financial management and resource consumption. The data collection method included the review of documents and financial statements, timing of all activities in the imaging department, and calculations based on the time-driven activity-based costing method, using Excel software, with the elimination of the cost of unused resources. Results: The study found that the total cost was mostly below the approved tariffs, with the main cost components being 34% manpower, 23% overhead, 22% equipment, and 15% consumables. The findings indicated that only 58% of resource provisioning expenses played a role in determining the total cost of services. Conclusion: The findings of this research suggest that reducing the unused capacity of resources and organizational reforms can decrease the total cost of services, increase profitability, and optimize resource usage to enhance the quality of hospital services.